Water Quality and Anopheles gambiae Larval Tolerance to Pyrethroids in the Cities of Douala and Yaoundé (Cameroon) - Billy Tene Fossog; Edmond Kopya; Cyrille Ndo; Benjamin Menze-Djantio; Carlo Costantini; Flaubert Njiokou; Parfait Awono-Ambene; Christophe Antonio-Nkondjio (Journal of Tropical Medicine)
The poor management of the urban environment in sub-Saharan Africa is affecting Anopheles gambiae susceptibility to insecticides. A study was undertaken to assess the influence of breeding sites physicochemical parameters on malaria vectors population tolerance to insecticides. A total of 18, 262 larvae collected from 104 breeding sites were exposed to diagnostic concentrations of permethrin and deltamethrin. Larvae originating from cultivated sites were more tolerant than larvae from polluted or nonpolluted sites. No significant difference was observed between polluted and nonpolluted sites. Field larvae were 142 to 325 times and 6.08 to 9.57 times more tolerant to deltamethrin and permethrin, respectively, than larvae of the A. gambiae Kisumu strain used as control. A low but significant correlation was detected between physicochemical parameters and larval insecticide tolerance. Cultivated sites were negatively and significantly correlated to larval tolerance to both deltamethrin (r=−0.421; P<0.0001) and permethrin (r=−0.392; P<0.0001). Dissolved oxygen (r=+0.466; P<0.0001) and ammonia (r=−0.205; P=0.04) appeared significantly correlated to larval tolerance to deltamethrin. The data suggest a direct correlation between some characteristics from the breeding sites and larval tolerance to pyrethroids.